Analisis Preferensi Konsumen Terhadap Promo Potongan Harga Sebagai Dasar Pengembangan Strategi Supermarket X dan Y di Indonesia - Arifin, Andrea Syahzehan; Rasmini, Mas (Jurnal Ilmiah Wahana Pendidikan, 2024)
Sales promotion is an instrument of communication for retail companies to provide benefits in an attractive form to customers, and sales promotion is often referred to as a type of communication that plays an essential role in growing consumer interest. Price discounts are a form of sales promotion that is most in demand by consumers, so retail management also requires various information related to consumer preferences so that strategies can also be produced that suit the needs and characteristics of these consumers, which in this study is discussed is promo Z. The method used in This research is in the form of a quantitative descriptive method, and the data were obtained using primary sources derived from consumer survei results in the form of questionnaires with answer choices which, of course, are tailored to the needs of the company and secondary sources originating from discussions with various related parties. Based on the consumer survei results divided into levels of awareness and consumer preferences for the Z promo, the results are exciting and beneficial and form the basis for the company's future strategy.